ESTABLISHING THE SCHEME OF THE FAULTS IN SOUTH CENTRAL COASTAL REGION ON THE BASIS OF INTERPRETING THE GEOLOGICAL-GEOPHYSICAL DATA - Thanh, Bui Nhi; Hung, Duong Quoc; Luong, Nguyen Van; Diep, Nguyen Van; Dong, Mai Duc; Xuan, Bui Thị Thanh; Thanh, Nguyen Kim (Vietnam Journal of Marine Science and Technology, 2018)
The scheme of the faults in South Central coastal region was established on the basis of interpreting the high resolution shallow seismic data and the deep-seismic data, in combination with the previous studies on geodynamics, tectonic evolution, geological hazards of the South Central coastal region. The fault systems were formed based on updated geophysical, geomorphological, tectonophysic and remote sensing data, including 19 faults in 3 directions: Sub-longitudinal (8 faults), NE-SW (7 faults) and NW-SE (4 faults)